Thoraco-sternopagus monster: a rare case of fetal dystocia in buffalo - PRASAD, J K; PRASAD, SHIV; KUMAR, AWADHESH; SINGH, G K (The Indian Journal of Animal Reproduction, 2023)
A rare case of dystocia due to the thoraco-stemopagus fetal monster in buffaloes was relieved by laparohysterotomy. Postmortem examination of fetus revealed an enlarged liver with two gall bladders.